Liberté et gouvernement chez Montesquieu - Slongo, Paolo (Conceptos Históricos, 2018)
By placing at the heart of our reading the idea that political society can only be conceived as the relations that are formed within it -but not only with itself- , it is possible to paint a portrait of Montesquieu in an old school style and, in the very same movement, also in a contemporary style -provided that we agree with the premise that our horizon is, by means of the tension inflicted into this initiative by modern political philosophy, the inclusion of the Social into the Law-. The very idea of justice, as the political community’s aspirational drive, must be taken, in Montesquieu’s work, as a general relation of the community with the whole. According Durkheim himself, Montesquieu founded the true social science. He just failed in giving it a name. Maybe he did not want to choose among the myriad of things that creates constitutional relations. Notwithstanding, he certainly founded the social science -it is enough just to notice the richness of his analysis-. The source of this knowledge is political society.